Fraud detection suicide: the dark side of white-collar crime. Issue 4 (3rd October 2016) - Brody, Richard G.; Perri, Frank S.
Abstract : Purpose: The purpose of this paper is to explore the issue of suicide, a violent act against one's self, as it relates to white- and red-collar crimes. White-collar crime can be described as nonviolent crime committed for financial gain. Red-collar crime describes a situation where a white-collar criminal commits an act of violence, often murder, to silence someone who is in a position to report a fraud they have perpetrated. Previous research has not addressed the issue of suicide, as it relates to white- and red-collar crime. Design/methodology/approach: The analysis is conceptual, focusing on the historical underpinnings of white- and red-collar crime and reviewing the evolution of white-collar criminals. Sources of information consisted of published news media, scholarly articles and articles retrieved from the web. Findings: A suicide may be linked, directly or indirectly, to a financial crime. Law enforcement must be careful not to jump to conclusions, as there is a possibility that a staged suicide has occurred. Originality/value: Law enforcement individuals may want to consider an additional motive when investigating a suicide, especially when the victim has some type of connection to a known fraud. This type of connection may not be readily apparent and may require a new approach on the part of a law enforcement investigation.